2021
DOI: 10.1021/acscentsci.1c01032
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Memory Polymers Designed in View of Thermomechanical Energy Storage and Conversion Systems

Abstract: Effective temporary shape fixation by strain-induced formation of supramolecular nanostructures enables high energy density one-way shape-memory polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Shape memory polymers (SMPs) can change their configuration and macroscopic shape between permanent and temporary states 31 , 32 . The temporary shape is usually obtained through mechanical deformation under certain conditions, such as heating above the glass transition temperature ( T g ), followed by shape fixation upon cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory polymers (SMPs) can change their configuration and macroscopic shape between permanent and temporary states 31 , 32 . The temporary shape is usually obtained through mechanical deformation under certain conditions, such as heating above the glass transition temperature ( T g ), followed by shape fixation upon cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Trapping such processing-induced stretched states, e.g., by a temperature quench or rapid removal of solvent, generates states of nonequilibrated polymers, yielding improved material properties like high toughness and yield stress, strongly enhanced Young’s modulus, and substantial birefringence. Furthermore, it has been suggested that deformed polymers may serve as an “energy sink” by transforming local stresses into changes in conformational entropy, thereby storing energy in their deformation modes . Feeding energy into states of deformed polymer chains may potentially introduce responsiveness by releasing (part of) the stored energy. …”
Section: Introductionmentioning
confidence: 99%